VD_FINDINFO HC / 2012 / 578 vom 13. September 2012 - VD Tribunal cantonal (2012)
OBLIGATION D'ENTRETIEN, MESURE PROVISIONNELLE, ASSISTANCE JUDICIAIRE, PREUVE FACILITÉE | 176 al. 1 ch. 1 CC, 117 CPC (CH), 276 al. 1 CPC (CH), 308 CPC (CH), 317 CPC (CH)